LABELLING OF M-TRIMETHYL SILYLPHENYL)-ETHYLIDENE-1, 1-BISPHOSPHONATE WITH 99mTc AND ITS EVALUATION AS AN IMAGING AGENT - Sajid, K. M.; Mahmood, R. (The Nucleus, 2012)
Technetium-99m labeled phosphates and phosphonates have since long been in use for bone imaging to diagnose bone infection, bone metastasis and bone fracture. 131I -labeled bisphosphonates have also been prepared for targeted radiotherapy of bone metastasis. Although animal experiments show good accumulation of bisphosphonates in bone. The agent has never been tried in humans because of high gamma and beta energy. The agent must first be tested in humans using a relatively safe radioisotope. Technitium-99m ( 99mTc) a radioisotope with relatively low gamma energy and short half-life can serve as a good label. Whether 99mTc-labeled bisphosphonates can be used as good imaging agents is another aspect that needs further investigation. A study was therefore, conducted to label m-trimethyl silylphenyl)-ethylidene-1, 1-bisphosphonate with 99mTc and standardize the labeling procedure. The labeling procedure involved reduction of technetium (TcO4 - ) with stannous chloride followed by chelation of technetium with bisphosphonates. Radiochemical purity was checked by paper chromatography. Pyrogenicity was checked by administration of the labeled compound into rabbits. The stability of the compound was determined by noting the radiochemical binding at several intervals of half an hour after preparation. Biodistribution of the agent was studied by injecting the labeled compound into rabbits. The results showed that the compound could be labeled with 99mTc without any difficulty. The ease of binding was excellent. There was more than 95% binding of technetium with the compound and the labelled compound was reasonably stable for 5 hours after labeling. The rectal temperature remained stable during this period, which showed that the animal accepted the compound and there were no pyrogenic reactions. Biodistribution studies on rabbit showed that accumulation of agent was poor in bones and the labeled compound remains in blood even after 4 hours. Comparison of bone scans with those obtained with 99mTc-MDP and 99mTc-PYP showed that the compound can not compete with these bone agents as for as the quality of bone scans is concerned. Tc99m -MDP still remains the superior bone scanning agent. However, the retention of relatively higher quantities of radiopharmaceutical in blood for long period showed that the compound could serve as a good blood pool-imaging agent. Purification of HPLC (high pressure liquid chromatography) could also improve the distribution properties of the compound. This needs further studies.